MAIN THEORIES OF EXTRASYSTOLE PATHOGENESIS - Jaqsimuratova Xurliman tatlimuratovna (Bright Mind Publishing, 2025)
It is shown that supraventricular extrasystole can be single or paired, and also have an allorhythmic character. In this case, the interval between the extrasystolic P wave and the preceding P wave of the sinus rhythm is usually strictly fixed. The signs of the genesis of supraventricular arrhythmia are studied.
Keywords: Supraventricular extrasystole, pulmonary, sinus, rhythm, postextrasystolic pause, block, teeth, compensator.